Exploring The Blended Learning Experience Among 21st Century Language Learners - Nursyuhada' Ab Wahab; Melor Md Yunus; Azni Mohamed Zain (The UPM Press, 2024)
In line with the Fourth Industrial Revolution, the world is facing technological transformation in which the Internet, cloud computing, and social media are creating different opportunities and challenges for formal education systems, specifically in relation to tertiary level education. This advancement has improved learningenvironments in universities, particularly in language teaching and learning. However, the dependency on teachers to facilitate the learning process is still crucial despite the various technological tools used. Thus, the blended learning approach is adopted to cater to the needs of millennial learners. A case study (focused on the implementation of features in a blended learning approach) used in an English for Specific Purpose (ESP) course at a Malaysian public university ispresented to illustrate the benefits gained through this mode of learning. This study includes an in-depth discussion of how students benefitted from the combination of traditional face-to-face learning and online teaching modes in language learning. Among the findings of this study, it was discovered that the combination of these two methods managed to encourage students to become independent learners, enabled them to gain easy access to course materials, and assisted them in utilising up-to-date technological tools in their learning processes.